Law Enforcement Against Destructive Fishing Crimes at the Regional Marine Police Directorate - Tuasuun, Ronald; Hehanussa, Deassy Jacomina Anthoneta; Adam, Sherly (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Destructive fishing activities carried out by fishermen generally use explosives (fish bombs), and the use of toxic materials to catch fish. The use of these materials results in damage to coral reefs and the surrounding ecosystems. Therefore, the role of the Directorate of Marine Police of the Maluku Police is needed in law enforcement of the crime of destructive fishing.Purposes of the Research: The purpose of this research is to study and analyze law enforcement against the crime of destructive fishing at the Directorate of Marine Police of the Maluku Police.Methods of the Research: The research method used is a type of normative juridical research, which uses a legal approach, a conceptual approach and a case approach. The source of legal materials is primary legal materials and secondary legal materials, the collection of legal materials through literature studies, processing and qualitative analysis of legal materials.Results Main Findings of the Research: The results showed that law enforcement of destructive fishing crimes carried out by the Directorate of Marine Police of Maluku Police is currently maximized and running well in accordance with applicable legislation. However, in law enforcement against destructive fishing, there are several factors that influence law enforcement, namely the legal factors themselves (laws and regulations); law enforcement factors; factors of facilities and facilities that support law enforcement; community factors.